Antibacterial Activity of Terminalia mantaly Stem Ethanol Extract as Hand Sanitizer Gel - Evi Sovia; Hernandi Sujono; Rinaldi Farizi; Sutrisno Sutrisno; Adilfi Risma Nurhadianti; Yenny Febriani Yun (Althea Medical Journal, 2023)
Background: Hand sanitizers generally contain alcohol. However, it can cause dry and irritated skin. Therefore, it is necessary to find antibacterial alternatives that are safe for the skin. One of the plants that has antibacterial activity is Terminalia mantaly (T. mantaly). This study aimed to investigate the antibacterial activity of ethanol extract and hand sanitizer gel of T. mantaly.